2021
DOI: 10.1038/s41419-021-03407-2
|View full text |Cite
|
Sign up to set email alerts
|

Acidic fibroblast growth factor attenuates type 2 diabetes-induced demyelination via suppressing oxidative stress damage

Abstract: Prolonged type 2 diabetes mellitus (T2DM) produces a common complication, peripheral neuropathy, which is accompanied by nerve fiber disorder, axon atrophy, and demyelination. Growing evidence has characterized the beneficial effects of acidic fibroblast growth factor (aFGF) and shown that it relieves hyperglycemia, increases insulin sensitivity, and ameliorates neuropathic impairment. However, there is scarce evidence on the role of aFGF on remodeling of aberrant myelin under hyperglycemia condition. Presentl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 78 publications
0
20
0
Order By: Relevance
“…The development of insulin resistance affects oxidative stress in diabetic mice, leading to a significant increase in the levels of reactive oxygen species (ROS) and MDA in mice ( Li et al, 2021 ). Previous studies have proven that a large number of antioxidant enzymes in organisms, such as SOD, T-AOC and GSH-PX, can suppress oxidative stress by scavenging ROS levels ( Liu S. W. et al, 2020 ; Wu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…The development of insulin resistance affects oxidative stress in diabetic mice, leading to a significant increase in the levels of reactive oxygen species (ROS) and MDA in mice ( Li et al, 2021 ). Previous studies have proven that a large number of antioxidant enzymes in organisms, such as SOD, T-AOC and GSH-PX, can suppress oxidative stress by scavenging ROS levels ( Liu S. W. et al, 2020 ; Wu et al, 2021 ).…”
Section: Resultsmentioning
confidence: 99%
“…However, it is still need to further explore the potential target of pyroptosis in DPN treatment. Our study found that fibroblast growth factor 1 (FGF1) expression is significantly inhibited after DPN, and exogenous FGF1 could alleviate DPN by alleviating oxidative stress in SCs (Li et al, 2021). Moreover, FGF21 and FGF10 also show significant therapeutic potential in peripheral nerve injury, both of which can reduce oxidative stress and promote neurological recovery.…”
Section: Diabetic Peripheral Neuropathymentioning
confidence: 86%
“…38 Growing evidence has also shown that aFGF can ameliorate hyperglycemia, increase insulin sensitivity, and relieve neuropathic impairment. 39 The existing imaging methods have limited effectiveness for evaluating acute SCI during transient axonal dysfunction and spinal shock. However, neuroelectrophysiological techniques show high sensitivity and accuracy and can allow quantitative measurement of the degree of SCI and clarify the characteristics of SCI-induced functional loss.…”
Section: Discussionmentioning
confidence: 99%
“… 38 Growing evidence has also shown that aFGF can ameliorate hyperglycemia, increase insulin sensitivity, and relieve neuropathic impairment. 39 …”
Section: Discussionmentioning
confidence: 99%